Abnormal COX2 Protein Expression May Be Correlated with Poor Prognosis in Oral Cancer: A Meta-Analysis. (16th June 2014) - Wang, Zhi-Ming; Liu, Jie; Liu, Hong-Bo; Ye, Ming; Zhang, Yu-Fei; Yang, Dong-Sheng
Abstract : Background. The prognostic significance of COX2 for survival of patients with oral cancer remains controversial. Thus, the meta-analysis was performed in order to identify COX2 expression impact on prognosis of oral cancer. Method. Relevant literatures were searched using the following electronic databases without any language restrictions: Web of Science, the Cochrane Library Database, PubMed, EMBASE, CINAHL, and CBM. Version 12.0 STATA software (Stata Corporation, College Station, Texas, USA) was used for the current meta-analysis. Odds ratios (ORs) and hazard ratios (HRs) with their corresponding 95% confidence interval (95% CI) were also calculated to clarify the correlation between COX2 expression and prognosis of oral cancer. Results. Final analysis of 979 oral cancer patients from 12 clinical cohort studies was performed. The meta-analysis results show that COX2 expression in cancer tissues was significantly higher than those in normal and benign tissues (all P < 0.05). Combined HR of COX2 suggests that positive COX2 expression has a shorter overall survival (OS) than those of negative COX2 expression ( P < 0.05). Conclusion. The meta-analysis study shows that elevated COX2 expression may be associated with the pathogenesis of oral cancer and with a worse prognosis in oral cancer patients.